An exploratory factor analysis of factors affecting safety performance in Malaysian paramedic training institutes / Intan Suraya Noor Arzahan ... [et al.] - Noor Arzahan, Intan Suraya; Ismail, Zaliha; Yasin, Siti Munira; Azhar, Zahir Izuan (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Safety performance at the government paramedic training institution includes determining what elements might impact the improvement of safety performance and contribute to a preventive safety culture inside the institute. This research intends to investigate and identify the elements that impact safety performance at the Malaysian paramedic training institution. By examining the literature, many elements that affect safety performance have been identified as having a global impact. Using survey questionnaires, exploratory factor analysis (EFA) was used for dimension reduction, and five clustering components of the 48 indicators were identified and discussed. The five factors were management commitment, safety system, risk management, safety competency, and workers’ involvement in safety. It was discovered that these factors substantially affect the safety performance of paramedic training institutions in Malaysia. The findings of this research will aid paramedic training institutes in boosting their safety performance, hence creating a safer work environment for employees with fewer hazards and accidents.